Assessing capacity strengthening needs for policy analysis in Malawi - Babu, Suresh Chandra; Mataya, Charles (International Food Policy Research Institute, 1996)
Considerable investments have been made in the past three decades in developing and strengthening institutions and the necessary human capacity for analyzing and implementing development policies. However, the impact of such efforts in creating a sustainable core of policy analysts has been limited. This paper is an attempt--both methodological and operational--to assess the capacity strengthening needs in food, agriculture and natural resource planning and policy analysis in Malawi. The main objective of the needs assessment exercise was to identify the constraints affecting individual and institutional performance in policy analysis and policy-making in the decision making systems involved in food, agriculture and natural resources sectors of Malawi. The expected outputs of the needs assessment exercise included: improved understanding of the technical and managerial roles of policy analysts in the decision making systems; improved understanding of the policy analysis skills required for the jobs and the associated gaps in them; increased understanding of the organizational constraints in implementing the results of policy analysis; and suggestions for improving the roles of policy analysts through training.